2021
DOI: 10.21037/jgo-21-147
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA small nucleolar RNA host gene 7 facilitates the proliferation, migration, and invasion of esophageal cancer cells by regulating microRNA-625

Abstract: Background: Esophageal cancer (EC) is a highly aggressive malignant tumor, of which esophageal squamous cell carcinoma (ESCC) constitutes the main subtype. Long non-coding RNA (lncRNA) small nucleolar RNA host gene 7 (SNHG7) has been extensively studied in many tumors and has been confirmed to be an oncogene; however, it has yet to be investigated in an ESCC study. Therefore, this study intended to uncover the role of SNHG7 in ESCC.Methods: Quantitative real-time polymerase chain reaction was applied to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Wild‐type DLGAP1‐AS2 and the mutant‐type DLGAP1‐AS2 were cloned into the firefly luciferase gene reporter vector pmirGLO (Promega). The pmirGLO‐DLGAP1‐AS2‐WT or pmirGLO‐DLGAP1‐AS2‐MUT was co‐transfected into U2OS and Soas2 cells with miR‐451a mimics or NC mimics for 48 h, and then detected using the luciferase reporter assay system (Promega) 25 . Similarly, wild‐type HK2 and mutant‐type HK2 were cloned into the firefly luciferase gene reporter vector pmiRGLO (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild‐type DLGAP1‐AS2 and the mutant‐type DLGAP1‐AS2 were cloned into the firefly luciferase gene reporter vector pmirGLO (Promega). The pmirGLO‐DLGAP1‐AS2‐WT or pmirGLO‐DLGAP1‐AS2‐MUT was co‐transfected into U2OS and Soas2 cells with miR‐451a mimics or NC mimics for 48 h, and then detected using the luciferase reporter assay system (Promega) 25 . Similarly, wild‐type HK2 and mutant‐type HK2 were cloned into the firefly luciferase gene reporter vector pmiRGLO (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…The pmirGLO‐DLGAP1‐AS2‐WT or pmirGLO‐DLGAP1‐AS2‐MUT was co‐transfected into U2OS and Soas2 cells with miR‐451a mimics or NC mimics for 48 h, and then detected using the luciferase reporter assay system (Promega). 25 Similarly, wild‐type HK2 and mutant‐type HK2 were cloned into the firefly luciferase gene reporter vector pmiRGLO (Promega). The pmirGLO‐HK2‐WT or pmirGLO‐HK2‐MUT was co‐transfected with miR‐451a mimics, miR‐451a mimics plus DLGAP1‐AS2, or NC mimics into U2OS and Soas2 cells.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zhang (18) et al found that lncRNA SNHG7 was highly expressed in gastric cancer tissues and was closely associated with the proliferation, apoptosis, invasion and metastasis of gastric cancer cells. Among the 7 candidate lncRNAs, only HAND2-AS1 and SNHG7 had been reported as prognostic factors in ESCC (19,20); the rest of lncRNAs were identified as prognostic signatures in BC for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In malignant pleural mesothelioma (MPM) (34,35) and thyroid cancer (TC) (36,37), miR-625 was found to be upregulated. It is downregulated in bladder cancer (38), nasopharyngeal carcinoma (NPC) (39), lung cancer (40)(41)(42)(43)(44)(45)(46), HCC (47), cervical cancer (CC) (48,49), osteosarcoma (50), melanoma (51)(52)(53)(54), laryngeal squamous cell carcinoma (LSCC) (55), acute myeloid leukemia (AML) (56), BC (57)(58)(59), glioma (60,61), esophageal cancer (EC) (62)(63)(64), clear cell renal cell carcinoma (65), GC (66)(67)(68)(69)(70), and pancreatic ductal adenocarcinoma (PDAC) (71). In colorectal cancer (CRC), the expression of miR-625 seems to vary, being either high or low.…”
Section: Mir-625 In Cancers Aberrant Expression Of Mir-625 In Cancersmentioning
confidence: 99%